Rare primary dyslipidaemias associated with low LDL and HDL cholesterol values in Portugal - Alves, Ana Catarina; Miranda, Beatriz; Moldovan, Oana; Santo, Raquel Espírito; Gouveia Silva, Raquel; Soares Cardoso, Sandra; Diogo, Luísa; Seidi, Mónica; Sequeira, Silvia; Bourbon, Mafalda (Frontiers in Genetics, 2023)
Background: Dyslipidaemia represents a group of disorders of lipid metabolism, characterized by either an increase or decrease in lipid particles, usually associated with triglycerides, LDL cholesterol (LDL-C) and/or HDL cholesterol (HDL-C). Most hyperlipidaemias and HDL deficiencies confer an increased cardiovascular risk, while hypolipidaemia, such as abeta or hypobetalipoproteinemia, may present different manifestations ranging from poor weight progression to neurological manifestations. The aim of this study is to present 7 cases with rare dyslipidaemias associated with low LDL or low HDL cholesterol values, referred to our laboratory for the genetic identification of the cause of the dyslipidaemia. Methods: Lipid profile was determined for each individual in an automated equipment Integra Cobas(Roche). Molecular analysis was performed by NGS with a target panel of 57 genes involved in lipid metabolism (Sure select QXT, Agilent) and samples were run in a NextSEQ Sequencer(Illumina). Only genes associated to rare forms of low HDL-c or LDL-c were analysed for this work, namely: ABCA1, APOA1, LCAT, SCARB1, APOB, PCSK9, MTTP, SAR1B, and ANGPTL3. All rare variants (MAF<5%) found in these genes were confirmed by Sanger sequencing. Results and discussion: This study includes 7 index cases (IC), with the following clinical diagnoses: Fish Eye Disease (1), Hypoalphalipoproteinemia (1) and Abetalipoproteinemia (ABL) / Familial Hypobetalipoproteinemia (FHBL) (5). We have identified one IC with a compound heterozygosity in LCAT causing Fish Eye Disease and one IC with a variant in ABCA1 in homozygosity causing Tangier disease. We found variants causing homozygous FHBL in 2 IC, one of whom has an undescribed pathogenic variant in homozygosity in APOB (c.12087+1G>A) and the other is a possible compound heterozygous for APOB variants c.2604+1G>A and c.4651C>T/p.(Gln1551*). In two patients only a variant in heterozygosity (c.3365delG/p.(Gly1122Vfs*62) and c.11095A>T/p.(Arg3699*)). In the remaining patient, no variants were identified. Conclusions: NGS proved to be a fundamental key for genetic testing of rare lipid disorders, allowing us to find the genetic cause of disease in 6/7 patients with low HDL-c and LDL-c. Patients with these rare conditions should be identified as early as possible in order to minimize or prevent clinical manifestations. The unsolved case is still under investigation.